The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.25035/ijare.01.03.06
|View full text |Cite
|
Sign up to set email alerts
|

Jumping Abilities and Swimming Grab-Start Performances in Elite and Recreational Swimmers

Abstract: This study examined the relationships between the performances of a swimming grab start and each of countermovement jump for distance, countermovement jump for height, squat jump for distance, and squat jump for height. Nine elite and 7 recreational female swimmers performed 6 trials in each of the 4 jumping techniques and six 25-m freestyle sprints after a grab start. Elite participants performed significantly better in the start performances, and this was attributed to the greater horizontal impulse. Correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 4 publications
3
34
1
5
Order By: Relevance
“…On the other hand our results confirm the findings of some previous studies which showed that on land tests were more related to shorter times, i.e. time to swim to 5 m or solely to the above water phase of start (Benjanuvatra et al, 2007). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand our results confirm the findings of some previous studies which showed that on land tests were more related to shorter times, i.e. time to swim to 5 m or solely to the above water phase of start (Benjanuvatra et al, 2007). …”
Section: Discussionsupporting
confidence: 92%
“…Two distinct actions must be optimized during the block phase: a reaction to the start signal and a force impulse generated over the starting block (Benjanuvatra et al, 2007; Vantorre et al, 2014). A high force impulse results in a high push-off velocity and long flight distance meaning that the block phase strongly influences the flight and entry phases.…”
Section: Introductionmentioning
confidence: 99%
“…Die unterschiedlichen Befunde könnten mit den unterschiedlichen Messmethoden erklärt werden 6. Insgesamt geht aus den vorliegenden Befunden hervor, dass unabhängig von der Absprungtechnik ein flacher Absprung zu einer guten Startleistung beiträgt 7. In ihrem Beitrag "Start right -a biomechanical review of dive start performance" verweisen Lyttle und Benjavanutra (2004) in ihrer Diskussion der bisher sehr uneinheitlichen Befundlage auf ein Argument vonHay (1988), demgemäß intraindividuelle Vergleiche der Absprungtechniken bei ein und derselben Stichprobe stets mit der bevorzugten als auch mit der nicht bevorzugten Starttechnik5 Unklar bleibt, warum Miller et al beim Abflug von einer völlig gestreckten Körperhaltung ausgehen.…”
unclassified
“…Even though, recent studies (Benjanuvatra, Edmunds, & Blanskby, 2007;Beretic et al, 2013;Cronin & Sleivert, 2005;Cronin, Jones, & Frost, 2007;Ďurovic, Beretic, & Okicic, 2015;Fig, 2010;Garrido et al, 2010;Haycraft & Robertson, 2015;Morouco, Gonzáles-Badillo, & Garrido, 2012) proved, that higher explosive power should correlate with higher performance, it was not confirmed in the case of our swimmer.…”
Section: Discussionmentioning
confidence: 53%